2006
DOI: 10.1007/s10565-006-0140-y
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin-induced oxidative mitochondrial cardiotoxicity

Abstract: The anticancer agent Adriamycin (ADR) has long been recognized to induce a dose-limiting cardiotoxicity. Numerous studies have attempted to characterize and elucidate the mechanism(s) behind its cardiotoxic effect. Despite a wealth of data covering a wide-range of effects mediated by the drug, the definitive mechanism remains a matter of debate. However, there is consensus that this toxicity is related to the induction of reactive oxygen species (ROS). Induction of ROS in the heart by ADR occurs via redox cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
287
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(302 citation statements)
references
References 57 publications
(54 reference statements)
10
287
0
5
Order By: Relevance
“…Scale bar corresponds to 10 μm vitro studies using primary cardiomyocytes (Gabrielson et al 2007;Solem et al 1996;Zhou et al 2001) or other cell lines (L'Ecuyer et al 2001;Spallarossa et al 2004) have been widely reported in the literature. From the different models used, some conclusions are common to all: (a) Dox is activated at the mitochondrial level, forming a semiquinone radical, and (b) Dox causes oxidative stress in cardiac cells that particularly affects mitochondria (Berthiaume and Wallace 2007;Wallace 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar corresponds to 10 μm vitro studies using primary cardiomyocytes (Gabrielson et al 2007;Solem et al 1996;Zhou et al 2001) or other cell lines (L'Ecuyer et al 2001;Spallarossa et al 2004) have been widely reported in the literature. From the different models used, some conclusions are common to all: (a) Dox is activated at the mitochondrial level, forming a semiquinone radical, and (b) Dox causes oxidative stress in cardiac cells that particularly affects mitochondria (Berthiaume and Wallace 2007;Wallace 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of DOX's cardiotoxicity is complex and may involve oxidative (2,3), nitrosative and nitrative stress (4,5), mitochondrial dysfunction/ toxicity (1,(6)(7)(8), dysregulation of various metabolic (9) and lipid signaling pathways (10)(11)(12), activation of various stress kinases and cell death mechanisms (both apoptotic and necrotic) (13), triggering of secondary inflammation and remodeling (14), eventually culminating in cardiac dysfunction and heart failure (1,15).…”
Section: Introductionmentioning
confidence: 99%
“…However, the chronic administration of this drug can induce toxicity to nontarget tissues, cardiotoxicity being the best known side effect [2]. DOX-induced cardiotoxicity has been attributed to a number of effects, including the direct inhibition of key transporters involved in ion homeostasis, alterations in cellular iron and calcium metabolism, disruption of sarcoplasmic reticulum function, mitochondrial dysfunction, and apoptotic cell loss [3]. The mechanisms underlying these events seem to be linked to an increased production of reactive oxygen species (ROS) and oxidative damage [3].…”
Section: Introductionmentioning
confidence: 99%
“…DOX-induced cardiotoxicity has been attributed to a number of effects, including the direct inhibition of key transporters involved in ion homeostasis, alterations in cellular iron and calcium metabolism, disruption of sarcoplasmic reticulum function, mitochondrial dysfunction, and apoptotic cell loss [3]. The mechanisms underlying these events seem to be linked to an increased production of reactive oxygen species (ROS) and oxidative damage [3]. Oxidative stress results from an imbalance between the generation of ROS and reactive nitrogen species and their removal by the cellular antioxidant system [4] and has been implicated in many neurodegenerative disorders [5,6].…”
Section: Introductionmentioning
confidence: 99%